HUBUNGAN KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR MATA PELAJARAN EKONOMI PADA SISWA KELAS X SMA SANTUN UNTAN PONTIANAK - Ulfa, Shofiana; Warneri, Warneri; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to determine the relationship of emotional intelligence with the learning outcomes of class X students of SMA SantunUntan Pontianak. The method used is descriptive method, with a form of association relationship study research. Data collection techniques used are indirect communication techniques with data collection tools in the form of questionnaires and documentary study techniques with data collection tools in the form of student learning outcomes scores. The data used were analyzed with descriptive analysis of Percentage, Average, Product Moment Correlation, and t test. The population in this study were students of class X SantunUntan High School Pontianak, amounting to 61 students, while the research sample used was 38 students. From the results of the research conducted, it can be concluded that: (1) the level of emotional intelligence of students in economic subjects in Class X SantunUntan High School Pontianak is classified as good, (2) student learning outcomes in economic subjects Class X SMA SantunUntan Pontianak good category, ( 3) there is a significant relationship between emotional intelligence and student learning outcomes in economic subjects class X SantunUntan High School Pontianak.Keywords: Emotional Intelligence and Learning Outcomes